Antifungal and antioxidant activities of Ag@FeO-NPs@Chitosan preparation by endophyte Streptomyces aureofaciens - Haggag, W. M.; Eid, M. M. (International Journal of Agricultural Technology, 2022)
Biological control using beneficial microorganisms is nowdeveloped for reducing the plant pathogens. Nanoparticles with specific functions have been produced and represented an economical alternative to agochemical through the natural methods of nanoparticle formation. Biosynthesis of Ag@FeO-NPs@Chitosan preparation by Streptomyces aureofaciens was performed against some soil borne pathogenic fungi i.e. Fusarium oxysporum, F. solani, F. subglutinans, Rhizoctonia solani and air borne pathogenic fungi i.e. Botrytis cinerea, Colletotrichum gloeosporioides, Alternaria solani and Aspergillus niger . To conceive the formation of Ag@FeO-NPs@Chitosan, ultraviolet-visible (UV-Vis) spectroscopy for the biosynthesis of core–shell nanoparticle and fourier transform infrared (FTIR) spectroscopy analysis were done for constructing the structure of nano-composite. Scanning transmission electron microscopy (STEM), and scanning transmission electron microscopy (STEM) micrographs evidenced that the size of synthesized nanoparticles is less than 50 nm. As a result, the data showed that the produced core–shell hemtite @Ag nanoparticles are super-paramagnetic. The chitosan is formed in the outer shell of the formula spontaneously due to the presence of chitin in the fungus cell membrane. In vitro bioassay, Ag@FeO-NPs@Chitosan preparation by Streptomyces showed distinct antifungal against all plant pathogens, and inhibited the growth and spores germination. Antioxidant activities as reducing power measurement, DPPH (1,1-Diphenyl-2- picrylhydrazyl) radical scavenging activity, nitric oxide scavenging activity, ABTS free radical scavenging activity and total phenolics contents were greatly increased. Synthesized Ag@FeO-NPs@Chitosan preparation by S. aureofaciens is demonstrated remarkable potential for using as antifungal compound to combat plant diseases. Chitosan is a good source for the preparation of bionanoparticle materials for industry and applications